1,5-Diphenyl-4,8-bis(3-phenylpyrazol-1-yl)pyrazabole - Kunrath, F. A.; Casagrande, O. L.; Toupet, L.; Carpentier, J. F. (Wiley-Blackwell, 2005)
The six-membered B(2)H(4) ring of the title compound, C(36)H(30)B(2)N(8), adopts a slightly distorted boat conformation, with the terminal B substituents in a trans orientation. One 3-phenylpyrazolyl group is in an equatorial position, whereas the second is in an axial position with respect to the plane defined by the B atoms.